Recepa e injertación del clon eet-116 y resiembra en un lote de cacao (theobroma cacao) ESPAM-MFL. - Santana Cedeño, José Filiberto (2012)
The research invesgation was developed in the field of MFL ESPAM of cocoa between October 2010 and October 2011 we had like objective renew a batch of cocoa (theobroma cacao) by agronomic practices recepa ,grafting and replanting using the TSE -116 clone for which were divided into phases with the following : phase 1 diagnostic of evaluating features such as planting of the plantation area age plant neight, seed spacing, number of plants and number of spaces then proceedec to the recepa making the cut to 40 cm soil in the form of bezel covering the wound with fungicide cupric after 30 days were evaluated the emission shoots which were chosen as those tha appeared up to 15 cm soil, phase 2 began with the selection of scions of clone EET-116 of the clonal garden and proceded to the grafting two basal shoots for plant for spike lateral evaluating it 21 days later where no arrest is regrafting in the same outbreak in the frespaces pollinateere planted TSE – 116.the result was an emission of outbreaks of 11.5, shoots for plant, of 285 recepadas, which had an arrest rate 75.4% and 100%reinjertacion ln conclusion we can say that by using this practice was a plantation renewed, even recommending it for older plantations following a phytosanitary management according to the methods described.